Heterogeneity of Patenting Activity and Its Implications for Scientific Research - Dirk Czarnitzki; Wolfgang Glänzel; Katrin Hussinger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
The increasing commercialization of university discoveries has initiated a controversy on the impacts for future scientific research. It has been argued that an increasing orientation towards commercialization may have a negative impact on more fundamental research efforts in science. Several scholars have therefore analyzed the relationship between publication and patenting activity of university researchers, and most articles report positive correlations. However, most studies do not account for heterogeneity of patenting activities ranging from university patents to corporate patents. While the former may have closer links to basic research, this is not what we expect from the latter. We argue that such efforts will indeed distract scientists from other activities, as collaborations with companies are usually assumed to have an applied character and do not necessarily coincide with basic research tasks. This paper investigates the incidence of patenting and publishing distinguishing between different types of patents for a large sample of professors active in Germany. Our results show that, while university patents as well as patents assigned to not-for-profit institutions complement publication quantity and quality, corporate patents yield negative effects.
Keywords: O32; O31; O34; 330; Entrepreneurial universities; academic inventors; industry-science linkages; patents; technology transfer